Interpolation-based reconstruction methods for tomographic imaging in 3D positron emission tomography - Li, Yingbo; Kummert, Anton; Boschen, Fritz; Herzog, Hans (Zielona Góra: Uniwersytet Zielonogórski)
Positron Emission Tomography (PET) is considered a key diagnostic tool in neuroscience, by means of which valuable insight into the metabolism function in vivo may be gained. Due to the underlying physical nature of PET, 3D imaging techniques in terms of a 3D measuring mode are intrinsically demanded to assure satisfying resolutions of the reconstructed images.
Keywords: tomographic reconstruction; three-dimensional positron emission tomography; Fourier slice theorem; frequency